Alur Perdagangan Hiu sebagai Komoditas Ikan Hias dari Provinsi Bali - Ni Made Putri Handayani; Pande Gde Sasmita Julyantoro; I Ketut Wija Negara (Fakultas Kelautan dan Perikanan Universitas Udayana, 2018)
This study objectives were to investigate the track of shark trade from Bali Province, the exports volume of shark trade during 2015-2016, the length of sharks; species exported in the ETP category; and the effectiveness of shark trade license by BPSPL Denpasar based on EAFM analysis. This study used exploration method with questionnaires, interviews and secondary data from BPSPL Denpasar. The results showed that the track of shark trade started from when the shark is caught by the fishermen which purchased by exporter companies, then they had to get shipment recommendation letter from BPSPL Denpasar and fish health certificate from BKIPM Class I Denpasar, then sharks was brought to I Gusti Ngurah Rai International Airport for final check and ready to be exported to the destination country. During 2015-2016 there were 559 sharks from the species of Carcharhinus melanopterus, Triaenodon obesus, Orectolobus maculatus, Atelomycterus marmoratus, Chiloscyllium plagiosum and Halaelurus maculosus that have been exported to the 12 destination countries. The EAFM analysis of lengths indicated that the shark's size was at a very young until adult age. Meanwhile, the EAFM analysis of ETP species shows there were 4 shark types of Near Threatened, 1 type of Least Concern status and 1 type of Not Evaluated. Finally the result of EAFM analysis on the effectiveness of shark trade license by BPSPL Denpasar showed that the decision was well executed and run effectively, and so far the shark fishery management at Bali Province is applied successfully.